THE INFLUENCE OF PROFITABILITY, ASSETS STRUCTURE, FIRM SIZE, BUSINESS RISK, SALES GROWTH, AND DIVIDEND POLICY ON CAPITAL STRUCTURE - Triyono, Triyono; Kusumastuti, Anindita; Palupi, Indarti Diah (Riset Akuntansi dan Keuangan Indonesia, 2019)
The aim of the research is to find out the influence of profitability, asset structure, company size, business risk, sales growth, and dividend policy to the capital structure of manufacturing companies listed on the IDX. The research sample was determined by purposive sampling method based on the criteria of manufacturing companies that were registered for three consecutive years and distributed dividends at least once. 117 have been selected as sample. This study uses multiple linear regression models. In this study it can be concluded that Profitability (ROA), Company Size (UP), Business Risk (RISK), Sales Growth (PP) affect to the Capital Structure (DER). Asset Structure (SA) and Dividend Policy (DPR) do not affect to the Capital Structure (DER).